1958
DOI: 10.1099/00221287-18-3-670
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inoculum Size on Inhibition Zones in Agar Media Using Staphylococci and Streptomycin

Abstract: The conditions under which this theoretical formula is expected to be true are necessarily those under which the initial assumptions are most nearly approached. The most important are : an antibiotic which diffuses freely through a non-interfering medium from a reservoir of constant concentration, and an inoculation of a determined number of metabolizing organisms which, after a constant lag period, multiply at a constant rate. Constancy of temperature and of media composition are also important. Many workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

1963
1963
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
(23 reference statements)
1
18
0
2
Order By: Relevance
“…1958). In order to verify that M. luteus is in the log phase at T c , a growth curve was experimentally generated which is shown in Fig 4…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1958). In order to verify that M. luteus is in the log phase at T c , a growth curve was experimentally generated which is shown in Fig 4…”
Section: Resultsmentioning
confidence: 99%
“…1958) have shown that the critical time of the test organism can be approximately related to its lag period ( L ) and generation time ( G ) when grown under standard conditions. Their model was verified experimentally with indicator organisms Staphylococcus aureus (Cooper et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique can be combined with a two-dimensional contour map to show the effects of drug concentration and time [36]. Both methods can provide important information for PK/PD analysis [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Stab inoculation was useful for detecting such activity; it allowed inhibition which would otherwise not have been observed and directed attention to the importance of limiting diffusion in order to maintain high local antibiotic concentrations. This is important when examining organisms with similar growth rates, since a critical antibiotic concentration may be attained before growth of the sensitive population reaches a resistant level, as was found by Cooper, Linton & Sehgal (1958). These inhibitory agents were heatresistant, able to pass through cellophan, and showed considerable specificity in action when tested against resistant staphfylococcal variants.…”
Section: Discussionmentioning
confidence: 99%